Nanodroplet array platform for integrated synthesis and screening of MEK inhibitors: a miniaturized approach to early drug discovery - Seifermann, Maximilian; Höpfner, Julius; Bauer, Liana; Varadharajan, Divya; Schmidt, Stefan; Fröhlich, Björn; Wellenhofer, Benjamin; Luchena, Charlotte; Hopf, Carsten; Popova, Anna A.; Levkin, Pavel (Angewandte Chemie. International edition, 2025)
Early-stage drug discovery relies on high-throughput screenings, which are costly and time-intensive, limiting access for academic laboratories and small companies. A key bottleneck is the lack of miniaturization and the separation of compound synthesis from screening. We present a nanoliter droplet array platform integrating synthesis, characterization, and cell-based screening of 325 MEK (mitogen-activated protein kinase kinase) inhibitors, targeting the MAPK/ERK (mitogen-activated protein kinase/extracellular signal-regulated kinase) pathway, implicated in colorectal and pancreatic cancer. The platform enables on-chip synthesis, MALDI-MSI (matrix-assisted laser desorption/ionization-mass spectrometry imaging) characterization, and cell-based screening within 200 nL droplets containing 20 nmol starting material (∼4 ng final compound), and only 300 cells per droplet. Screening identified 46 compounds with higher cytotoxicity than mirdametinib, a clinically approved MEK inhibitor. Molecular docking revealed a shared allosteric binding mechanism, indicating non-competitive ATP inhibition. Synthesis and screening of all 325 compounds were completed within 7 days, requiring <10 mg of reactants, <250 µL solvent, and ∼100 µL of cell suspension (∼100,000 cells in total). Our results demonstrate that integrating miniaturized combinatorial synthesis and biological screening in a single platform can accelerate early-stage drug discovery while reducing cost and resource use.
Zuerst veröffentlicht: 18. August 2025
Gesehen am 14.01.2026